Tourism as a Public Good – Local Government Perspective - Katarzyna Kopczewska (Contemporary Economics)
Development of tourism should be based on common participation of local governments, enterprises and communities. Strong impulse for building and enlargement of infrastructure and tourism service was given by European funds, for which local governments and firms can apply. This support should be analyzed two-fold: subjective „who” and geographical „where” funds were used and what is their potential. The article presents spatial analysis of tourism development in Poland from the perspective of public sector.